2018
DOI: 10.19044/esj.2018.v14n24p464
|View full text |Cite
|
Sign up to set email alerts
|

Efficacite Du Baume De Cajou Contre Les Chenilles Carpophages Du Cotonnier Au Nord Du Benin

Abstract: Cotton remains the main source of foreign exchange for Benin. This study aims to contribute to increased yield of organic cotton through the evaluation of the effectiveness of cashew balm as an alternative method of management of carpophagous pests of cotton. The experimental setup consists of Fisher Blocks with 6 objects in 4 repetitions. The objects compared are '' Unprocessed '', the Agri-bio-pesticide dosed at 1 l / ha, two concentrations (1% and 2%) of the hot and cold-extracted cashew balm. Linear mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…For seed cotton yield, the results showed that neem oil combined with chilli and soap and B thuringiensis resulted in 853.53 kg/ha for organic cotton and 531.25 kg/ha for untreated cotton. This result on seed cotton yield is in agreement with that of [6] who showed that Agri-bio-pesticide which is a neem based organic pesticide improved yield compared to the untreated control. Treatments with neem oil in organic cotton crop resulted in a yield increase of 312.28 kg/ha compared to the untreated.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For seed cotton yield, the results showed that neem oil combined with chilli and soap and B thuringiensis resulted in 853.53 kg/ha for organic cotton and 531.25 kg/ha for untreated cotton. This result on seed cotton yield is in agreement with that of [6] who showed that Agri-bio-pesticide which is a neem based organic pesticide improved yield compared to the untreated control. Treatments with neem oil in organic cotton crop resulted in a yield increase of 312.28 kg/ha compared to the untreated.…”
Section: Discussionsupporting
confidence: 91%
“…This result is in line with the results of other authors [39] [40] who have shown significant entomopathogenic activity of B. thuringiensis on several insect species. In the case of Capsicum frutescens L, its performance in plant protection results from the presence of alkaloids, saponins and flavonoids contained in the fruits of this botanical species [6]. Concerning beneficial insects, they are represented by ladybirds, spiders, ants, praying mantises and notably P. lutescens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cashew balm is also used as a bio-insecticide [20] against crop pests such as caterpillars. (Helicoverpa armigera, Earias spp., Diparopsis watersi, Spodoptera littoralis, Pectinophora gossypiella, Thaumatotibia leucotreta) in cotton [21] , coleopteran (Collosobruchus maculatus) in cowpea stock [22] . Cashew nut oil is also obtained from cashew nut which is mainly used in pharmacology and cosmetics [19] .…”
Section: Industrial Usementioning
confidence: 99%
“…Ces pesticides engendrent des problèmes de pollution de l'eau et des sols, les intoxications alimentaires et les atteintes sanitaires, l'apparition du phénomène de résistance ainsi que l'interférence négative des pesticides sur la faune et le contrôle biologique d'autres ravageurs (Biaou et al, 2003 ;DIREN, 2003 ;Toe, 2004, Azonkpin et al, 2018a. De plus, la pression constante qu'exerce le consommateur pour une agriculture plus saine et durable, a poussé à l'intensification des recherches pour la mise au point de méthodes alternatives de production plus respectueuses de l'environnement (Chougourou et al, 2012 ;Fayalo et al, 2014 ;Togbé et al, 2014b ;Mehinto et al, 2015 ;Azonkpin et al, 2018b). C'est dans cette perspective que les pays producteurs de coton s'intéressent de plus en plus aux modes de production alternative comme la production de coton-graine biologique et équitable.…”
Section: Introductionunclassified